Interference Cancellation Using Replica Signal for HTRCI-MIMO/OFDM in Time-Variant Large Delay Spread Longer Than Guard Interval - Yuta Ida; Chang-Jun Ahn; Takeshi Kamio; Hisato Fujisaka; Kazuhisa Haeiwa (Journal of Electrical and Computer Engineering)
Orthogonal frequency division multiplexing (OFDM) and multiple-input multiple-output (MIMO) are generally known as the effective techniques for high data rate services. In MIMO/OFDM systems, the channel estimation (CE) is very important to obtain an accurate channel state information (CSI). However, since the orthogonal pilot-based CE requires the large number of pilot symbols, the total transmission rate is degraded. To mitigate this problem, a high time resolution carrier interferometry (HTRCI) for MIMO/OFDM has been proposed. In wireless communication systems, if the maximum delay spread is longer than the guard interval (GI), the system performance is significantly degraded due to the intersymbol interference (ISI) and intercarrier interference (ICI). However, the conventional HTRCI-MIMO/OFDM does not consider the case with the time-variant large delay spread longer than the GI. In this paper, we propose the ISI and ICI compensation methods for a HTRCI-MIMO/OFDM in the time-variant large delay spread longer than the GI.